A fundamentação das decisões judiciais sob a perspectiva das ciências cognitivas: limites e possibilidades para a formação racional do convencimento motivado - Pinho, Samara de Oliveira (2018)
This paper aims to present the necessity to establish a dialogue between Juridical Science and the Cognitive Sciences, extracting some theoretical tools that are indispensable to a realistic comprehension to the rational formation from motivated stipulation, in order to concede a scientific support to its own fundamental construction to judicial decisions. Therefore, a study about operative justification should be conducted, before, by a minimal understanding, about the functioning and conceptualization of the mind and human cognitions, which is known that jurisdictional activity is a manifestation of the own exercise of cognition, reason which the development of a research about the theme on judicial justification, without the analysis of the influences on mental aspects from the judging, would not demonstrate so productive. It is relevant the knowledge about the specific concepts of Cognitive Sciences, especially institutes and basic appliances from this field of study to convey support to the exam of legal reasoning of legal decisions, in consideration to a few limits and possibilities found, related to the human mind reports (and, equally, the cognition itself). Based on these presumptions, in accordance with the use of descriptive method, since bibliographical evaluation from the nation doctrine and international about the thematic, this research will focus, initially, on some notions about the human mind, rationale, unconscious, Cognitive Semantic, aspects apparently unusual to the Law, in which, at the end, will demonstrate closely connected to it, besides the results in a systemic gain and conceptual in the act of judicial interpretation and normative. Thereafter, it will confront the difference between justification and judicial decision, its counterpoints in the limitation of performance of the judging, investigating possible failures that the human thought could exhibit and how it can impact on jurisdictional matter. In conclusion, it will reflect in which way the junction between Cognitive Sciences and Legal Science can collaborate to the improvement to the study, application and, specifically, on the interpretation of norms related to the decisive legal ground.